Reflection of program documents in the media discourses and their impact on the public consciousness (Eurasian Journal of Philology Science and Education, 2018)
The article discusses the role of political discourse in the form of program documents and the discourse of the media as an active participant in political communication. The polyfunctionality andmultiplicity of political discourse and media discourse are analyzed on the basis of authentic texts –government policy documents. Political discourse and media discourse have many similarities, oftenoverlapping in their fields of application.The leading hypergenres of political discourse are listed and described: program documents, publicspeech politics, election campaign, corresponding to the main intention of the political discourse – thestruggle for power. By peripheral author relates political memoirs, an interview. At the same time, eachhyper-genre includes texts that form primary genres within the hyper-genre under consideration, as wellas peripheral genres.